Cervical Diskography Performed with a “Prong Deflector” for Improved Access to the Cervical Disk Spaces - Bartynski, Walter S.; Grahovac, Stephen Z.; Rothfus, William E. (American Journal of Neuroradiology, 2005)
Summary: The “prong deflector” tool improves accuracy and ease of access to the cervical disk spaces for use in cervical diskography. The tool allows control, deflection, and stabilization of vital neck structures (carotid artery, thyroid cartilages and pharynx) while allowing fluoroscopic visualization during needle insertion without direct operator radiation exposure. Use of the prong deflector resulted in marked reduction of fluoroscopy per cervical level studied because of more rapid access to disk space.